2006
DOI: 10.5483/bmbrep.2006.39.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Transduced Tat-α-Synuclein Protects against Oxidative Stress In vitro and In vivo

Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder and is characterized by the progressive loss of dopaminergic neurons in the substantia nigra. Although many studies showed that the aggregation of alpha-synuclein might be involved in the pathogenesis of PD, its protective properties against oxidative stress remain to be elucidated. In this study, human wild type and mutant alpha-synuclein genes were fused with a gene fragment encoding the nine amino acid transactivator of transcription (Tat) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
3
16
0
2
Order By: Relevance
“…Actually, asynuclein transfected cells were more resistant to the oxidative insult induced by DA, whereas cells transfected with a control vector behaved like wild-type ones. This finding was in agreement with the observation that expression of the TAT-a-synuclein fusion protein at sub-micromolar level is protective toward oxidative stress [61,62]. Increased viability was referred to a more than two-fold increase in the levels of DJ-1, a PD-related protein [63].…”
Section: Proteomics Of Cellular Models Ofsupporting
confidence: 80%
“…Actually, asynuclein transfected cells were more resistant to the oxidative insult induced by DA, whereas cells transfected with a control vector behaved like wild-type ones. This finding was in agreement with the observation that expression of the TAT-a-synuclein fusion protein at sub-micromolar level is protective toward oxidative stress [61,62]. Increased viability was referred to a more than two-fold increase in the levels of DJ-1, a PD-related protein [63].…”
Section: Proteomics Of Cellular Models Ofsupporting
confidence: 80%
“…The authors found increased expression of HSP70 in mice treated with both paraquat and Tat-␣ -syn, and this increase was directly dependent on the concentration of the wt Tat-wt-␣ -syn. They suggested that the decreased cell death was due to the increased level of HSP70, which was able to antagonize the oxidative cell stress [81] . To better reproduce the key feature of human PD transgenic ␣ -syn, animal models have been studied.…”
Section: ␣ -Synuclein (Snca Park1/4)mentioning
confidence: 99%
“…In animal PD models, the induced increase in HSP70 synthesis protects against soluble ␣-syn toxicity and oxidative stress [81].…”
Section: Uch-l1 (Park5)mentioning
confidence: 99%
“…Although Tat fusion proteins have been used to deliver therapeutic proteins in vitro and in vivo, the exact mechanism remains unclear. In previous studies, we have shown in vitro and in vivo that various transduced fusion proteins efficiently protected against cell death Choi et al, 2006a;2006b;Eum et al, 2004;Kim et al, 2009;Kwon et al, 2000).…”
Section: Introductionmentioning
confidence: 88%
“…Prolonged exposure to ROS contributes significantly to the pathological processes of a number of human diseases and is a major factor in the cause of various neurodegenerative disorders including PD (Hald and Lotharius, 2005;Pong et al, 2001;Rastogi et al, 2006;Tamagno et al, 2003). In a previous study, we showed that the administration of a herbicide paraquat (1,1′-dimethy-4,4′-bipyridinium) triggers selective dopaminergic neuronal cell death and the exposure of mice to which is an effective model for studying the pathological aspects of PD (Choi et al, 2006a). Also, another study has suggested that paraquat is associated with an increased risk of PD (Synder and D'Amato, 1985).…”
Section: Introductionmentioning
confidence: 99%